POTENTIAL AND STRATEGY OF HALAL ECONOMIC DEVELOPMENT IN THE HALAL INDUSTRY SECTOR - Lubis, Rahmat Husein (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to analyze the potential and strategies for developing the halal economy in the halal industry sector concept 4.0. This type of research is descriptive qualitative research, a study by examining several sources. The research sources used are several sources such as books, scientific journals, encyclopedias, literature, scientific works, and websites that are related to this research. The object of research in this study is in the form of writing or text related to the potential and strategies for developing the halal economy in the halal industry sector. The results of this study indicate that the potential for the halal economy in the halal industry sector is enormous if using the halal industry 4.0, such as increasing production efficiency, increasing transparency and security, forms of product and service innovation, and increasing global market access. As well as the provision of halal certification has become an important tool for expanding access to global markets. For the halal economic development strategy in the halal industry sector such as; first, the government needs to adopt a pro-halal policy. Such as providing incentives and facilities for halal industry players. Second, increased investment in research and development of halal technology is needed to improve the quality and diversification of halal products. Third, effective promotion and marketing must be implemented to increase consumer awareness about halal products